Supramolecular ultra-short carboxybenzyl-protected dehydropeptide-based hydrogels for drug delivery - Veloso, Sérgio R. S. (2021)
Self-assembled peptide-based hydrogels are promising materials for biomedical research owing to biocompatibility and similarity to the extracellular matrix, amenable synthesis and functionalization and structural tailoring of the rheological properties. Wider developments of self-assembled peptide-based hydrogels in biomedical research and clinical translation are hampered by limited commercial availability allied to prohibitive costs. In this work a focused library of Cbz-protected dehydrodipeptides Cbz-L-Xaa-Z-ΔPhe-OH (Xaa= Met, Phe, Tyr, Ala, Gly) was synthesised and evaluated as minimalist hydrogels. The Cbz-L-Met-Z-ΔPhe-OH and Cbz-L-Phe-Z-ΔPhe-OH hydrogelators were comprehensively evaluated regarding molecular aggregation and self-assembly, gelation, biocompatibility and as drug carriers for delivery of the natural compound curcumin and the clinically important antitumor drug doxorubicin. Drug release profiles and FRET studies of drug transport into small unilamellar vesicles (as biomembrane models) demonstrated that the Cbz-protected dehydropeptide hydrogels are effective nanocarriers for drug delivery. The expedite and scalable synthesis (in 3 steps), using commercially available reagents and amenable reaction conditions, makes Cbz-protected dehydrodipeptide hydrogels, widely available at affordable cost to the research community.